Infall and accretion of substructure in hydrodynamical simulations of galaxy clusters - Haggar, Roan (2022)
The evolution of galaxies is heavily influenced by the environment in which they are found. Dense regions of the Universe can quench a galaxy's star formation by removing its gas, and transform a galaxy's morphology from being disk-dominated to bulge-dominated. Galaxy clusters represent the most extreme example of this: compared to the cosmic field, these highly dense environments contain a much greater fraction of red, elliptical galaxies. However, a subtlety of this is that a galaxy's evolution is not just driven by the environment in which it is currently found, but is also influenced by the environments through which it has previously passed. For example, a galaxy in the outskirts of a cluster may also have been quenched during pre-processing, meaning that it was accreted onto the cluster through a cosmic filament or as a member of a group, both of which can quench star formation. Alternatively, it could be a backsplash galaxy: one that has passed through the dense cluster environment in the past, but subsequently left and now resides in the cluster outskirts.